A pilot randomized controlled trial of controlled cord traction to reduce postpartum blood loss - Althabe, Fernando (2009)
OBJECTIVE: To evaluate whether controlled cord traction (CCT) for management of the third stage of labor reduced postpartum blood loss compared with a "hands-off" management protocol. METHODS: Women with imminent vaginal delivery were randomly assigned to either a CCT group or a hands-off group. The women received prophylactic oxytocin. The primary outcome was blood loss during the third stage of labor. RESULTS: In total, 103 women were allocated to the CCT group and 101 were allocated to the hands-off group. Median blood loss in the CCT group and the hands-off group was 282.0 mL and 310.2 mL, respectively. The difference in blood loss (-28.2 mL) was not significant (95% confidence interval, -92.3 to 35.9; P=0.126). Blood collection in the hands-off group took 1.2 minutes longer than in the CCT group, which may have contributed to this difference. CONCLUSION: CCT may reduce postpartum blood loss. The present findings support conducting a large trial to determine whether CCT can prevent postpartum hemorrhage.